Retrospective Analysis of Electrocautery Procedures in the Dermatology Outpatient Clinic of Bali Mandara Hospital Based on Medical Record Data - I Putu Bagus Normantia Cahaya Putra; Luh Putu Dina Wahyuni (Journal La Medihealtico, 2026)
Electrocautery is a minor surgical procedure that uses electrical energy to generate heat for tissue destruction and hemostasis. This procedure is commonly used in the Dermatology Outpatient Clinic of Bali Mandara Hospital for the management of Condyloma Acuminata, Verruca Vulgaris, and Seborrheic Keratosis. This study aimed to analyze the pattern and management of electrocautery procedures for these dermatological cases based on medical record data from 2022 to 2025. This study used a retrospective descriptive design based on secondary data obtained from the medical records of patients who underwent electrocautery procedures at the Dermatology Outpatient Clinic of Bali Mandara Hospital. Data were analyzed using descriptive statistics, cross-tabulation, and annual case growth analysis with Microsoft Excel and SPSS version 27. The results showed a total of 322 cases, consisting of 78 cases of Condyloma Acuminata (24.22%), 138 cases of Verruca Vulgaris (42.86%), and 106 cases of Seborrheic Keratosis (32.92%). Verruca Vulgaris was the most frequently treated condition during the study period. The findings also indicate that each condition requires different electrocautery techniques according to lesion characteristics, anatomical location, and clinical considerations. Electrocautery is a suitable procedure for the management of Condyloma Acuminata, Verruca Vulgaris, and Seborrheic Keratosis at Bali Mandara Hospital. However, the technique should be adjusted to the characteristics of each case to optimize treatment outcomes and ensure patient safety.